2020
DOI: 10.21203/rs.3.rs-32024/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Nutritional status of school children living in Northern part of Sri Lanka

Abstract: Background Nutritional status is an important indicator for measuring quality of life in children. A region that is recovering from war will face many problems related to nutrition. Very few studies have addressed the nutritional problems in school-going children. This study was undertaken to identify the prevalence of various nutritional problems and to assess the correlation of it to certain socio-demographic factors. Methods Community based cross sectional study using multistage stratified proportionate c… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 9 publications
0
11
1
Order By: Relevance
“…Values above the 50 th percentile in our children were slightly lower, than those found in children from Canada, and slightly higher in children from Great Britain and Brazil [11,[22][23].…”
Section: Discussioncontrasting
confidence: 72%
“…Values above the 50 th percentile in our children were slightly lower, than those found in children from Canada, and slightly higher in children from Great Britain and Brazil [11,[22][23].…”
Section: Discussioncontrasting
confidence: 72%
“…The same findings by Wahid et al (2020) in Saronggi Subdistrict, Indonesia showed that there was no relationship between stunting events and the number of household members (13). The same study in Sri Lanka found family size did not contribute to stunting (6). The number of family members directly and indirectly will also affect the fulfillment of nutrition in the child.…”
Section: Number Of Family Membersmentioning
confidence: 83%
“…Stunting in early childhood has been shown to increase the risk of dying from childhood illnesses, impair cognitive development, decrease educational performance and reduce employment opportunities later in life. Stunting can later be accompanied by excessive weight gain, thereby increasing the risk of obesity and non-communicable disease (NCD) as an adult (6). Nutrition of schoolchildren is an index and prerequisite of national investment in the development of a nation's social capital in the future.…”
Section: Introductionmentioning
confidence: 99%
“…Obesity was predominantly seen in boys (4.2%) and it was significantly higher when compared to the girls (2.1%). (Sathiadas et al, 2020) A descriptive cross-sectional study done in Pokhara in 2020 showed that 12.49% of the students were overweight and 5.03% were thin. (Maskey et al, 2020).…”
Section: Rational Of the Studymentioning
confidence: 99%